ANALYSIS OF THE APPLICATION OF MARKET SEGMENTATION BASED ON GEOGRAPHICS, DEMOGRAPHICS, PSYCHOGRAPHICS, AND BEHAVIOR TOWARDS CUSTOMER INTEREST IN MADURA'S TYPICAL RICE AND FRIED CHICKEN RESTAURANTS IN KONAWE - Melati, Melati; Susanti, Anita (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze consumer segmentation in the traditional culinary business of a Madurese duck rice and fried chicken restaurant in Konawe Regency. This study used a descriptive qualitative method with data collection techniques including interviews, observation, and documentation. Informants consisted of the owner, employees, and customers who had visited the restaurant two or more times. The analysis was conducted based on four types of market segmentation: geographic, demographic, psychographic, and behavioral. The results of this study indicate that this restaurant has a fairly broad market segment, encompassing both local and out-of-town customers, with consumers predominantly students, office workers, and families. Authentic taste, affordable prices, and fast service are the main factors attracting customers. Geographic segmentation indicates potential for expansion due to the increase in out-of-town visitors on weekends. Demographic and psychographic segmentation indicate that customers have a high interest in traditional, spicy dishes. Behavioral segmentation indicates the presence of loyal customers and repeat purchasing patterns. These findings provide important recommendations for businesses to develop more effective marketing strategies tailored to the characteristics of their target market.